Manager Race and the Race of New Hires - Giuliano, Laura; Levine, David I.; Leonard, Jonathan (Journal of Labor Economics, 2009)
Using personnel data from a large U.S. retail firm, we examine whether the race or ethnicity of the hiring manager affects the racial composition of new hires. We exploit manager turnover to estimate models with store fixed effects and store-specific trends. First, we find that all nonblack managers-that is, whites, Hispanics, and Asians-hire more whites and fewer blacks than do black managers. This is especially true in the South. Second, in locations with large Hispanic populations, Hispanic managers hire more Hispanics and fewer whites than do white managers. We also examine possible explanations for these differential hiring patterns. (c) 2009 by The University of Chicago. All rights reserved.